Theories of international responsibility law / edited by Samantha Besson ; with the assistance of Mathilde Montaubin. - Besson, Samantha, 1973- (ASIL studies in international legal theory., 2022)
There is no issue more central to a legal order than responsibility, and yet the dearth of contemporary theorizing on international responsibility law is worrying for the state of international law. The volume brings philosophers of the law of responsibility into dialogue with international responsibility law specialists. Its tripartite structure corresponds to the three main theoretical challenges in the contemporary practice of international responsibility law: the public and private nature of the international responsibility of public institutions; its collective and individual dimensions; and the place of fault therein. In each part, two international lawyers and two philosophers of responsibility law address the most pressing questions in the theory of international responsibility law. The volume closes with a comparative 'world tour' of the responsibility of public institutions in four different legal cultures and regions, identifying stepping-stones and stumbling blocks on the path towards a common law of international responsibility.